2020
DOI: 10.3390/pathogens10010021
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ivermectin Treatment on the Frequency of Seizures in Persons with Epilepsy Infected with Onchocerca volvulus

Abstract: A clinical trial performed in the Democratic Republic of Congo (DRC), among persons with epilepsy (PWE) infected with Onchocerca volvulus treated with anti-seizure medication suggested that ivermectin reduces the seizure frequency. We assessed the effect of ivermectin treatment on seizure frequency in PWE with and without anti-seizure medication in three onchocerciasis endemic areas (Maridi, South Sudan; Aketi, DRC; and Mahenge, Tanzania). Pre- and 3–5 months post-ivermectin microfilariae densities in skin sni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…A possible explanation for this may be that ivermectin is believed by the affected communities to improve the NS outcome. Also, a recent study in onchocerciasis-endemic areas in sub-Saharan Africa suggested that ivermectin intake reduced seizure frequency in persons with epilepsy who are infected with O. volvulus [ 21 ]. Additionally, children with NS, because of their disabilities, may be more likely to be at home during ivermectin distribution compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…A possible explanation for this may be that ivermectin is believed by the affected communities to improve the NS outcome. Also, a recent study in onchocerciasis-endemic areas in sub-Saharan Africa suggested that ivermectin intake reduced seizure frequency in persons with epilepsy who are infected with O. volvulus [ 21 ]. Additionally, children with NS, because of their disabilities, may be more likely to be at home during ivermectin distribution compared to healthy controls.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the importance of molecular pathways investigation, from a clinical point of view the administration of IVM as an adjuvant therapy in epileptic patients suffering from parasitic diseases is also being investigated. In clinical studies, it has been determined that the coadministration of IVM in combination with drugs such as phenobarbital with GABAergic effects, can reduce the occurrence of seizures in these patients [ 26 , 28 , 66 ]. Therefore, it is very important to find drug interactions in order to make the treatment more effective, and additional studies in this field seem necessary.…”
Section: Discussionmentioning
confidence: 99%
“…However, ivermectin, an FDA‐approved drug, exerts as an activator of GIRK channel subunits (Chen et al, 2017; Su et al., 2016). Clinical studies have revealed that ivermectin can reduce the frequency of seizures and provide adjuvant therapy for refractory epilepsy (Diazgranados‐Sanchez et al., 2017; Dusabimana et al., 2020; Mandro et al., 2020). Ivermectin can also prevent SUDEP and cardiac disorders accompanying seizures by regulating cardiac IKACh current.…”
Section: Discussionmentioning
confidence: 99%